Inhibitory Effects of Euphorbia tirucalli Lineu (Euphorbiaceae) Diluted Latex on Human and Canine Melanoma Cells - Alves da Paz, Diego Pinha (Evid Based Complement Alternat Med, 2020)
Euphorbia tirucalli Lineu (Euphorbiaceae) is a tropical and subtropical ornamental and toxic plant. E. tirucalli produces a latex that is commonly used to treat neoplasms. This study aimed to evaluate the effects of diluted E. tirucalli latex (DETL) on human (SK-MEL-28) and canine (CBMY) melanoma cells. SK-MEL-28 (3 × 10(3) cells/well) and CBMY (6 × 10(3) cells/well) were cultivated in 96-well plates. The cells were treated with 50 μl/well of dilutions (1/2, 1/4, 1/8, 1/16, 1/32, 1/64, 1/128, 1/256, and 1/512) of a standard solution containing 1 mg/mL of the E. tirucalli latex (ETL) in DMEM. Control group cells received 50 μl/well of DMEM. After 24, 48, and 72 h of treatment, cell viability was assessed by the MTT assay. There was a significant decrease in viability at 48 and 72 hours after treatment for human melanoma cells and at 24, 48, and 72 hours for canine cells, mainly in higher dilutions of ETL. Human melanoma cells presented a typical U shape curve, characteristic of hormesis. To our knowledge, this is the first study showing inhibitory effects of DETL on canine melanoma cells. Therefore, DETL is a potentially new antineoplastic drug.